Application of Gamification in Ethnic Excellence-Based Character Education Programs - Carolina M.L.; Neneng Nuryati; Ediana Sutjiredjeki; Moh. Farid Najib; Sumeru; Sri N. Yuliyawati; Ade Hodijah (Journal of Games, Game Art, and Gamification, 2022)
This paper describes how the game is a tool to support the strengthening of character education for its users. In implementing the Independent Learning Education, Merdeka Campus, Bandung State Polytechnic, collaborated with the industry to apply gamification to the concept of character education and the nation's cultural values. Some of the objectives of this gamification activity are: (a) Getting the ethnic group’s information; (b) Providing users inspiration to develop themselves; (c) Growing a better direction mindset. The game developed is a web-based application (online gamification), so as many students/students and lecturers as possible can use the game to support strengthening character education and the nation's cultural values. The manual version of the video game content (prototype) is available, namely the 2021 research output containing Pancasila character content based on ethnic excellence. The elements of educational content in online gamification contain the results of identifying the prominent characters of 10 ethnic groups in Indonesia with the largest population (Dayak, Madura, Jawa, Sunda, Baduy, Batak, Banjar, Minahasa, Betawi, Minang). This study used three approaches which are Qualitative-Explorative, Qualitative-Descriptive, and Evaluation. The method used to know how gamification was implemented in character education and the nation's cultural values. It is hoped that gamification can integrate into the learning process for compulsory national subjects. Thus, students can become users and a market for the gamification industry.